4+ln(x+3)=3

Simple and best practice solution for 4+ln(x+3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+ln(x+3)=3 equation:


Simplifying
4 + ln(x + 3) = 3

Reorder the terms:
4 + ln(3 + x) = 3
4 + (3 * ln + x * ln) = 3
4 + (3ln + lnx) = 3

Solving
4 + 3ln + lnx = 3

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + 3ln + -4 + lnx = 3 + -4

Reorder the terms:
4 + -4 + 3ln + lnx = 3 + -4

Combine like terms: 4 + -4 = 0
0 + 3ln + lnx = 3 + -4
3ln + lnx = 3 + -4

Combine like terms: 3 + -4 = -1
3ln + lnx = -1

Reorder the terms:
1 + 3ln + lnx = -1 + 1

Combine like terms: -1 + 1 = 0
1 + 3ln + lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 8z-0.6=9z | | 5y-6=6y-1 | | -5j+(-2)+3= | | y--9=3/4(x-5) | | 2z+6=4z-3 | | =2u^10v^9w^8*w*9v^2*4u^9 | | (2m^2*n^-2*p^0/m^-2)^3= | | x^2*x^9= | | 0.3(0.2x-1)=0.4(0.5x-1) | | 2/5-7/20x=2 | | 3x-2=1/2=x/3 | | 5h+2(1-h)=-5 | | -4.3-k=-4.57 | | 16-6r=25-3r | | 4x-0.6-1.6x+2.9x+4= | | 6x+8=8x-3 | | -17.2=x-7.7 | | 6x+24+2x=68 | | n-6=n-8 | | 4-y/-17 | | 9+(-16)=-1 | | V/4=3/4 | | 2=b/8 | | 13x+88=107 | | f(x)=5x^2-19x-4 | | 6x-4=10+x | | 6x^2y^3/12x^3y | | x+5=-25 | | B+42=100 | | 8x^2-(-2-1)x+32=0 | | 8x^2-(2-1)x+32=0 | | 2a-9+a=90 |

Equations solver categories